Moderating the role of renewable energy use on the nexus between export diversification and ecological footprint in Sub-Saharan Africa - Atif Awad; Mohamed Albaity; Ray Saadaoui Mallek; Ilhan Ozturk (Sustainable Futures)
The Sub-Saharan Africa (SSA) region has implemented a variety of policies to diversify its exports so that it can achieve stable growth rate in per capita GDP. Despite their obvious impact on GDP growth rate, such policies are often overlooked in terms of their impact on the quality of the environment. This study examines the impact of export diversification on environmental quality conditional on renewable energy in 24 countries in the SSA region from 1995 to 2020 using Fully modified OLS (FMOLS) and dynamic OLS (DOLS) estimation methods. The findings showed that export diversification tends to degrade the quality of the environment, however, it can produce positive effects when coupled with the use of renewable energy. Further results from the Quantile Regression with Fixed Effects (QRF) technique showed that the above results are conditional on the distribution of the ecological footprint across countries. Our results indicate that for SSA countries, developing renewable energy in conjunction with diversifying of their exports is crucial for achieving sustainable development.